Peran Ikatan Notaris Indonesia dalam Mengawasi Etika Profesi Terkait Promosi Digital - Maria Arlena Oktaviana Sinaga (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Notary is a professional position whose position is determined by law, so he can make authentic deeds to meet the needs of authentic written evidence in society, and this is a form of duty as an extension of the state, therefore notary is called a noble position. In carrying out his position, a notary has authority, rights and obligations as well as prohibitions, and has a Notary Position Law and a Code of Ethics as a legal umbrella that regulates behavior both inside and outside of office. One of the notary's obligations is to keep the contents of the deed confidential, and one of the notary's prohibitions is to place advertisements. These two rules are often violated by notaries either through negligence or deliberately in order to seek existence and validation, by posting publications and promotions which are often persuasive in nature to attract and expand the reach of target clients, which of course aims to increase income, even though this is clearly contrary to norms and regulations, and also has the potential to cause unhealthy competition between fellow notaries. Legal enforcement of this problem needs to receive attention and law enforcement directly from the Indonesian Notary Association Organization through structural supervisors who are obliged to enforce the code of ethics and regulations therein. Supervisors should act actively to reprimand negligent notaries or simply publish and promote them in the media. social, in order to maintain the good name of the organization, maintain the dignity of the notary profession so that the public is not skeptical and assumes that the notary profession is a profession that is solely business oriented.